(untitled) (Philological Studies, 2019)
This paper examines the attitude towards tradition, especially medieval heritage in the poetry of Serbian postwar modernism, particularly in the poetry of Vasko Popa, Miodrag Pavlović, Ivan V. Lalić and Ljubomir Simović. We establish a definition of the term “Serbian-Byzantine heritage” and discuss its position in the history of Serbian literature. Since a reactivation of medieval lyrical patterns takes place within a creative tradition renewal in postwar poetry, the paper defines the inner impulses and forms of this renewal. Subsequently, it examines the nature of the lyrical return to medieval literature. We discuss the extent that the activation of poetic, aesthetic and ideological particularities of old Serbian literature owes to the tradition of European modernism and how much it actually represents an autochthone process determined by the internal logic of Serbian literature. Finally, we determine the distinctive medieval poetic views – lyrical totality, a desire for completeness, the idea of history – that were reactivated in the poetry of postwar modernism as an answer to contemporary poets’ questions.